Intersectionality and the United Nations World Conference Against Racism - Bakan, Abigail B.; Abu-Laban, Yasmeen (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
This article analyzes the 2001 World Conference Against Racism (WCAR) held in Durban, South Africa. Utilizing original interviews with civil society delegates in the United States and Canada, along with government documents and media and academic accounts, we challenge prevailing interpretations of the WCAR to show that it was an important space for expressions of an explicit feminist intersectionality approach, especially the intersection of racism with gender. Our findings demonstrate how intersectionality was relevant to the discussions of both state and civil society delegates and served to highlight racialized, gendered, and other discriminatory patterns. Based on this evidence, we argue that the WCAR process played a significant role in advancing a global conversation about intersectionality and therefore carried significant potential for advancing an anti-racist agenda for the twenty-first century. That this is not widely understood or highlighted has to do with challenges to the WCAR, particularly the withdrawal of key states from the process and a negative discourse concerning discussions and scholarly analysis of the WCAR process. We suggest that acknowledging the presence of intersectionality in the WCAR process gestures towards a more accurate historical record. It also suggests both the opportunities and constraints afforded by intersectional analysis in moments of transition and mainstreaming. As such, the “Durban moment,” and the WCAR more broadly, are highly relevant for the study of women, politics, and human rights over the first decade of the twenty-first century.